1999
DOI: 10.1248/cpb.47.971
|View full text |Cite
|
Sign up to set email alerts
|

Novel Potassium Channel Activators. II. Synthesis and Pharmacological Evaluation of 3,4-Dihydro-2H-1,4-benzoxazine Derivatives: Modification of the Aromatic Part.

Abstract: Three new series of analogues related to 3,4-dihydro-2H-1,4-benzoxazine derivative 1a were synthesized and evaluated for their potassium channel activating activity. In the first series I, where the 6,7-positions were disubstituted, it was found that an electron-withdrawing substituent was preferable at the 6 position, but either an electron-withdrawing or releasing substituent without bulkiness was tolerated at the 7 position. In the second series II, where several heterocycles were introduced into the 6,7-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Moreover, benzoxazines were useful compounds as starting materials for the synthesis of larger structures with valuable biological activities [4][5][6]. N-Dichloroacetylb enzoxazines were used as herbicide safeners [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, benzoxazines were useful compounds as starting materials for the synthesis of larger structures with valuable biological activities [4][5][6]. N-Dichloroacetylb enzoxazines were used as herbicide safeners [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…12 A re-investigation of the synthesis of 1,2,5-thiadiazole-3,4-carbonitrile (10) from diaminomaleonitrile showed that the most probable intermediate is monosulfinylamine 11, which eliminates water by the action of hydrogen chloride formed in the first step of the reaction; 13 In many cases, employing an organic base allows the reaction temperature to be reduced to room temperature, or to 0 • C, avoiding undesirable side processes. Usually triethylamine [14][15][16][17][18][19] or pyridine [20][21][22][23][24][25] in inert solvents such as dichloromethane, benzene, or chloroform were used. Typical examples were given in Scheme 3.…”
Section: From 12-diamines and Related Compoundsmentioning
confidence: 99%
“…At Yamanouchi, Matzumoto et al have conducted extensive research on K ATP CO 1,4-benzoxazines by investigating the different positions of this new scaffold through a multi-step SAR study [89][90][91]. Similar to 50, these 1,4-benzoxazines lack a hydroxyl group at the C-3 position resulting in achiral compounds that can be considered as a structural simplification of CRK.…”
Section: Benzoxazinesmentioning
confidence: 99%
“…The presence of a C-6/C-7 fused oxadiazole was already known to enhance potency in the benzopyran class [101]. The aromatic portion of the 1,4-benzoxazine scaffold was also modified by replacing the benzene ring with a pyridine one, giving a few examples of pyrido-1,4-oxazines [90]. An in vitro vasorelaxant activity comparable to that of CRK was observed for pyrido[4,3-b]-1,4-oxazine derivative 56, which bears an unusual borane group at the N-6 position; Fig.…”
Section: Benzoxazinesmentioning
confidence: 99%
See 1 more Smart Citation